Exploration of the psychosocial wellbeing aspect of vulnerable populations at risk in Kakuma Refugee Camp - Harun, Aisha Zainab; Maiyo, Angela; Jerotich, Sum Tecla (Research Journal in Advanced Social Sciences, 2022)
The refugee experience is characterized by exposure in one's country of origin to numerous traumatic incidents during migration and daily stressors after settlement in the camps as a result of natural disasters, wars and persecution on the basis of their race, religion, political beliefs and social identity, who cannot rely on their country of origin to protect them. Although numerous studies on deaths, illnesses and physical traumas resulting from wars and disasters have been performed, there are scanty longitudinal studies on how psychosocial issues influence refugees' mental health and the problem-specific interventions used to address mental ill health. The prevalence of mental illnesses among refugees keeps increasing in spite existing psychiatric treatment approaches used to resolve the particular concerns associated with mental health. The general objective of the study was to exploration of the psychosocial wellbeing aspect of vulnerable populations at risk in Kakuma refugee camp, Turkana County, Kenya.